Dementia incidence among a cohort of lebanese older adults: first incidence estimates from the Middle East and North Africa region - Chaaya, Monique; Assaad, Sarah; Darwish, Hala; Haber, Marc; Khoury, Rosemary; Saab, Dahlia; El Asmar, Khalil; Hajjar, Ramzi (Frontiers in Dementia, 2025)
Objective: To provide the first estimates of dementia incidence rates among elderly in Lebanon.Methods: The cohort established in 2013 consisted of 470 elderly from Beirut and Mount Lebanon, who consented to be followed-up. In 2017, we reached 341 participants/informants, achieving a response rate of 72.6%. The validated Arabic version of the 10/66 Dementia Research Group diagnostic tool was administered through face-to-face interviews. Direct age standardization was applied to the data using the Western European population distribution. Age-, sex-and locationspecific incidence rates were estimated.Results: After 3.5 years of follow up, 19 new cases of dementia were identified among 229 surviving participants. The crude incidence rate was 16.8 per 1000 p-y, and the age standardized rate was 20.5 per 1000 p-y. The incidence rate increased with age, going from 6.5 for those aged 65-74 years to 54.0 for those aged 85-89 years. Incidence rate was higher among females than males (20.7 vs.12.0), and higher in Mount Lebanon, as compared to the capital city Beirut, (19.5 vs.14.9). Conclusion: Dementia incidence rate was close to European and North American countries' estimates. The use of validated tools increased the internal validity of our results. A large cohort study is warranted to confirm these results.